2021
DOI: 10.1136/annrheumdis-2021-221490
|View full text |Cite
|
Sign up to set email alerts
|

Safety of vaccination against SARS-CoV-2 in people with rheumatic and musculoskeletal diseases: results from the EULAR Coronavirus Vaccine (COVAX) physician-reported registry

Abstract: ObjectivesTo describe the safety of vaccines against SARS-CoV-2 in people with inflammatory/autoimmune rheumatic and musculoskeletal disease (I-RMD).MethodsPhysician-reported registry of I-RMD and non-inflammatory RMD (NI-RMDs) patients vaccinated against SARS-CoV-2. From 5 February 2021 to 27 July 2021, we collected data on demographics, vaccination, RMD diagnosis, disease activity, immunomodulatory/immunosuppressive treatments, flares, adverse events (AEs) and SARS-CoV-2 breakthrough infections. Data were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
183
10
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(226 citation statements)
references
References 42 publications
(44 reference statements)
24
183
10
9
Order By: Relevance
“…The low rate of disease flares in RD was consistent with other publications [ 17 25 ]. It has been also suggested that the underlying risk of flare may differ among RD [ 17 ].…”
Section: Discussionsupporting
confidence: 92%
“…The low rate of disease flares in RD was consistent with other publications [ 17 25 ]. It has been also suggested that the underlying risk of flare may differ among RD [ 17 ].…”
Section: Discussionsupporting
confidence: 92%
“…Recently, a case-crossover study conducted by Yokose et al 2 revealed that recombinant herpes zoster vaccine (RZV) in the prior 2 days was associated with a twofold increased odds of gout flare when compared with no vaccine periods (adjusted OR 1.99; 95% CI 1.01 to 3.89). A study conducted by the European Alliance of Associations for Rheumatology Coronavirus Vaccine physician-reported Registry reported 4.4% of flare following mRNA vaccination in inflammatory/autoimmune rheumatic and musculoskeletal disease cases from 30 countries 3. However, to date, no systemic analysis, even real-world data, investigated the association between COVID-19 vaccine and gout flare.…”
Section: Introductionmentioning
confidence: 99%
“…However, a booster dose may be met with greater success in these patients and is, therefore, warranted [101]. It is also worthwhile mentioning that vaccination against SARS-CoV-2 is well-tolerated and generally safe in patients with inflammatory rheumatic diseases, including vasculitides, with low rates of breakthrough infections [102]. However, disease relapses have been reported in patients with AAV and HSP [103,104].…”
Section: Covid-19 In Patients With Vasculitidesmentioning
confidence: 99%